A study of factors affecting consumer purchase behaviour towards counterfeit products / Che Nur Asmani Amira Che Mohd Nawi ... [et al.] - Che Mohd Nawi, Che Nur Asmani Amira; Raja Yusup, Puteri Fazleen; Zainurrashid, Nurshahirah; Mohd Pisol, Nurul Husna (Unit Penerbitan, UiTM Kelantan, 2022)
Consumers behaviour towards purchasing counterfeit products will eventually lead to economic damage, affect the legitimate manufacturers and impact the industry and social cost. However, there is still limited research that have been conducted to investigate the predictors of consumer behaviour on counterfeit products. The aim of this study is to investigate the factors that can affect or influence the consumer purchase behaviour towards counterfeit products. This quantitative study randomly gathered one hundred and thirty-seven respondents from Universiti Teknologi MARA Kota Bharu Campus using random sampling technique. Online survey and questionnaire tool were used in this study for the collection method, and the data gathered were analysed using SPSS software. Findings showed that only personal gratification and social influence have the positive and significant relationship with consumer purchase behaviour on counterfeit products. The result from the findings, however, did not support price-quality inference on the consumer purchase behaviour. Personal gratification has been found to be the strongest factor for this research. Overall, this study reveals that consumers' desire for social attention, feeling of achievement, and need for social acceptance as the factors that mostly contributed to the behaviour to purchase counterfeit products.